Psychoneuroendocrinology of Sport and Exercise : Foundations, Markers, Trends. - Ehrlenspiel, Felix (Routledge research in sport and exercise science., 2012)
Psychoneuroendocrinology is the study of the interaction between hormones, the brain and human behaviour. This is the first book to examine psychoneuroendocrinology in the context of sport and exercise, offering a comprehensive review of current research and assessment techniques and highlighting directions for future research. The book explores the links between hormones and behaviour, and draws important conclusions for how their study will aid in the understanding of the bidirectional link between sport and behaviour, central to the psychology of sport and exercise. It presents the key horm.